Optimization of thermoelectric temperature control systems - A. I. Semilyak; T. E. Sarkarov; D. V. Evdulov; K. K. Nazarov (Вестник Дагестанского государственного технического университета: Технические науки, 2023)
Objective. The aim of the study is to study the methods of temperature control using the Peltier element in a given temperature range.Method. A heating method is applied using a Peltier element in a temperature control device of a small plate by regulating the current and using a cooling fan to reduce inertia.Result. A technique for controlling the Peltier element to maintain the required temperature is obtained, which is carried out using the PWM method generated by the ATmega2560 processor. The H-bridge on the L6203 integrated circuit switches the current direction and can control the current up to 5A on the Peltier element using a PWM signal.Conclusion. The resulting control algorithm provides an increase in the heating current on the Peltier until the temperature rises to a predetermined high temperature value, and then by changing the direction of the current, a cooling current is created on the Peltier element until the temperature of the copper plate drops to a predetermined low temperature. With repeated repetition of this sequence, the regularity of temperature changes is monitored to study the process of heating and cooling the plate using the Peltier element.